The Epochal Crisis of Global Capitalism - William I. Robinson (Vestnik RUDN. International Relations)
The conflict in Ukraine escalated in 2022 and the West’s radical political, military and economic response to it was but the coup de grâce of a decadent post-World War II western-centric order. However, the escalation of geopolitical tensions around the world in the wake its violent crackup is symptomatic of something more fundamental: the epochal crisis of global capitalism. The crisis is multidimensional, and its varied dimensions are interconnected. It is a structural crisis of overaccumulation, a political crisis of state legitimacy and capitalist hegemony, a social crisis of global social reproduction, a geopolitical crisis of escalating international conflict, and an environmental crisis that threatens the collapse of the planetary ecosystem. Unlike earlier crises of world capitalism (four crises are traditionally distinguished), we are reaching the historical exhaustion of the conditions for capitalist renewal. Capitalist reactivation may be possible in the coming years through redistributive and regulatory policies and through the application of new digital technologies, but such reactivation could not in the long run resolve the underlying contradictions of a decadent global capitalism. The author concludes that modern society is very far from a revolution against global capitalism, due to the underdevelopment of subjective and organizational conditions. The paper applies a comprehensive approach to the processes and phenomena under consideration, using the principles of comparative data analysis and critical assessment of information. The relevance of the topic of research is due to both the increase in political instability in the world, and the noticeable growth of rivalry and confrontation in global economic processes.